Evaluating the validity of tests to predict sprint and change of direction speed in para-athletes with brain impairments - Reina, R.; Beckman, E. M.; Connick, M. J.; Spathis, J. G.; Tweedy, S. M. (Adapted Physical Activity Quarterly, 2024)
Maximum running speed is a performance determinant in para-athletics and cerebral palsy football. Sixty international para-athletes with brain impairments completed five activity-limitation tests (standing broad jump, four bounds for distance, split jumps, 10-m speed skip, and running in place) and two criterion tests (40-m sprint and modified agility test). The same three tests (standing broad jump, four bounds for distance, and 10-m speed skip) that correlated with running performance in nondisabled runners (.67 < r < -.82; p < .05; 75% of variance) also correlated in para-athletes with brain impairments (.41 < r < -.62; p < .01; 55% of variance). Standing broad jump, four bounds for distance, split jumps, and running in place also correlated with change-of-direction speed (.43 < r < -.63; p < .01; 58% of variance). Results indicate that methods of classification for para-athletics with nondisabled runners are also valid with para-athletes with brain impairments, and new sport-specific relationships were found for assessing the performance of rapid and short sprints toward different directions, specific of a team para-sport like cerebral palsy football.